The Use of Sustainable Transition Metals for the Cycloaddition of Epoxides and CO2 under Mild Reaction Conditions. Issue 6 (11th July 2022) - Al‐Qaisi, Feda'a M.; Qaroush, Abdussalam K.; Okashah, Ibrahim K.; Eftaiha, Ala'a F.; Vasko, Petra; Alsoubani, Fatima; Repo, Timo
Abstract: Following green chemistry principles, we present a one pot synthesis of zinc curcumin complex as a homogeneous, sustainable catalyst for cyclic carbonate (CC) synthesis from CO2 and a variety of terminal and internal epoxides under 1 bar CO2 at 60 °C using DMSO as a solvent. Zinc curcumin (Zn‐Cur ) complex was identified via 1 H/ 13 C NMR and ATR‐FTIR spectroscopies, elemental analysis, ionic conductivity, and quantitative silver nitrate test to confirm a 1 : 1 molar ratio of metal to the ligand. Interestingly, Zn‐Cur showed an outstanding performance in catalysing the synthesis of renewable CCs including dimeric pinene and limonene carbonates. In this context, other metal complexes, including magnesium (Mg II ), calcium (Ca II ), and nickel (Ni II ) complexes showed good to excellent catalytic activity. Furthermore, a plausible reaction mechanism was investigated by density functional theory (DFT) calculations. The reaction was found to be overall exergonic by 39 kJ/mol and the rate determining step was CO2 insertion, which is in good agreement with the experimental findings. Abstract : The cycloaddition of CO2 to epoxide catalysed by zinc curcumin complex under balloon conditions is reported. The catalytic system showed good to excellent performance using a variety of terminal and renewable epoxides including pinene and limonene oxides. The proposed reaction mechanism was explored using density functional theory calculations.